Common Science Misconceptions among Junior, Secondary School, and College Freshmen: A Case Study in Dire Dawa City, Ethiopia - Goshu, Belay Sitotaw; Misganu, Tewodros; Abas, Ermias; Woldeamanue, Melaku Masresha; Ridwan, Muhammad (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2024)
The aim of this study was to clarify misconceptions about science subjects among middle school, high school, and first-year university students in Dire Dawa City. The sample size was 1,576 first-year middle school and university students in Dire Dawa, Ethiopia. The researchers asked each participant to write responses to open-ended questions about general concepts in biology, chemistry, and physics. The authors use descriptive analysis techniques. These results show that 31.6% of respondents and 49.9% of respondents incorrectly believe that breathing, breathing, and germs are always incorrect concepts. Furthermore, it was found that 33.0% of respondents had a misunderstanding that "seeds and eggs are not living things." 54.6% of respondents had a good understanding that carbon, oxygen, and hydrogen are essential elements for living things, but 26.1% said they did not have a clear understanding of this indicator. Moreover, it was found that 45.9% of respondents did not understand the concept of pressure and violence. 27.9% of respondents did not clearly understand this indicator, while the rest 20.6% understood about pressure. We concluded that the level of common misconceptions about science subjects among teachers, students' families, and students was very high. The government revised existing textbooks, and teachers need to review their teaching methods and work with school leaders to develop intervention mechanisms. Students should have a forum with their families to reflect on what students have learned and discuss science with their children. They are a source of dissemination of existing misconceptions.